FEATURES OF ACCOUNTING AUTOMATION AT ENTERPRISES IN UZBEKISTAN - G.T. Akhmedova (International Journal of Business, Law and Political Science, 2024)
The article analyzes the problems of accounting automation at enterprises, discusses possible ways to solve this problem. The author's approach defines a set of actions and measures aimed at improving the quality of accounting and simplifying accounting at enterprises in Uzbekistan.